RESPONSE OF GRAPE SEEDLINGS TO SUMMER PRUNING AND FOLIAR APPLICATION OF SOME NUTRENT - Al-Shemmery, Ghalib N.; Al-Obeidi, Mohammed A. (Diyala Agricultural Sciences Journal, 2018)
The study was conducted at private orchards in Bany-saad City-Diyala Province during the year 2015 to explore the effect of summer pruning and spraying Proline, iron, and zinc on vegetative growth and mineral content of grape transplant (Vitis vinifera L.) Cv. Halawani. Three kinds of summer pruning were used, the first was without pruning (T0). The second one stem was chosen and pruned by removing later shoots down the first weir (T1), and third one stem without pruning (T2). Spring treatment consisted of (water only, prolin at 150 mg l-1 iron at 100 mg l-1, zinc at 50 mg l-1). The treatment without pruning (T0) significantly increased in leaf content chlorophyll and zinc. While the (T1) significantly impacted in increasing in the stem height, chlorophyll and proline content. The T2 treatment increased significantly stem length and leaf area. Foliar application of iron caused a significant increase in stem height, leaf content iron and chlorophyll while spraying with zinc resulted in a significant increase in leaves content of zinc. Spraying of proline caused significant increase in leaf area and leaf content of proline.